Rancang Bangun Sistem Manajemen Aset Sekolah “S-Inventory” Berbasis Desktop - Maridho Anike Putri; Novi Ardiningtyas; Aurelia Firzatullah; Rizky Basatha; Nisa Dwi Septiyanti (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to design and develop a desktop-based School Inventory Information System as a solution to asset recording issues that have previously been conducted manually and are prone to errors. The application was developed using the Visual Programming paradigm with the VB.NET language on the Microsoft Visual Studio platform. Test result indicate that the application functions correctly and supports inventory administration activities without the need for external database integration. Consequently, this application is expected to serve as an effective tool for improving orderliness, accuracy, and transparency in school asset management.